Contemporary fiction : a very short introduction - Eaglestone, Robert (Very short introductions, 2013)
In thie Very short introduction Robert Eaglestone explores the major themes, patterns, and debates surrounding the contemporary novel. From genre, form, and experimentalism, to the relationship between globalization and terror, and the impact of technology, Eaglestone examines how contemporary fiction reflects both the world in which we live and the artistic concerns of writers and readers alike. -- Cover.